2020
DOI: 10.5005/jp-journals-10071-23477
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of Critically Ill Patients with COVID-19 in Western India: A Case Series

Abstract: A bstract Background The novel coronavirus, named SARS-CoV-2, was first described in December 2019 as a cluster of pneumonia cases in Wuhan, China. It has since been declared a pandemic, with substantial mortality. Materials and methods In our case series, we describe the clinical presentation, characteristics, and outcomes of our initial experience of managing 24 critically ill COVID-19 patients at a designated COVID-19 ICU in Western India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…A Double blind clinical trial on effectiveness of Remdesvir in covid 19 shows statistically insignificant results [ 3 ] WHO Solidary trial on repurposed antiviral drugs in covid 19 conclude that Remdesvir has no effect in hospitalized covid 19. [ 4 ] Some studies have reported that hypoxemic respiratory failure is one of the important cause of death in critically ill patients of covid 19[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Double blind clinical trial on effectiveness of Remdesvir in covid 19 shows statistically insignificant results [ 3 ] WHO Solidary trial on repurposed antiviral drugs in covid 19 conclude that Remdesvir has no effect in hospitalized covid 19. [ 4 ] Some studies have reported that hypoxemic respiratory failure is one of the important cause of death in critically ill patients of covid 19[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of patients in our study was 55.96 ± 14.52years which is similar to the study conducted by Chavali et al, in Maharashtra. [13] . Male preponderance was observed in our study as it was in other similar studies, probably due to high mobility and socialization among male gender when compared to females [10,13,14] .The mean duration symptoms before hospital admission was nearly 6 days in our study which was comparable to studies conducted by Bhatraju et al, (7 days)and Xie et al,(6 days) and few other studies thus indicating that delay in presentation more than 5 days of onset of symptom has high chances of severe illness and need for intensive care [7,15,16] .Though hypertension was significantly more prevalent among non survivors, we observed that the most common underlying co morbidity in all our patients was Diabetes Mellitus which was against several international studies that reported hypertension to be the predominant underlying comorbidity [5,8,14,17] .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of COVID was based on COVID RT-PCR and HRCT-CHEST suggestive of COVID. The complications such as ARDS, AKI, MODS, Myocarditis were defined as per standard reference book [13] Statistical Analysis:…”
Section: Data Collectionmentioning
confidence: 99%
“…Another study from Germany also reported an overall hospitalization of 12 (7–20) days for COVID-19 patients needing oxygen supplementation outside the ICU 35 . For critical patients, duration in the ICU for 9 (7-11) days has been reported 36 . A Belgian study reported the time between symptom onset and hospitalization to vary from 3-10.4 days 37 .…”
Section: Methodsmentioning
confidence: 99%